Identification of the double-bond position in fatty acid methyl esters by liquid chromatography/atmospheric pressure chemical ionisation mass spectrometry - Vrkoslav, Vladimír; Cvačka, Josef (Journal of chromatography. A, 2012)
Fatty acid methyl esters (FAMEs) were analysed by reversed-phase HPLC coupled with atmospheric pressure chemical ionisation (APCI) mass spectrometry. The chromatographic separations of the FAMEs were optimised using acetonitrile or binary acetonitrile gradients and C18 or C30 columns. The gas-phase reactions of acetonitrile and unsaturated FAMEs in the APCI source provided [M+C(3)H(5)N](+·) adducts. When fragmented, these adducts yielded diagnostic ions, allowing the unambiguous localisation of double bonds. The formation and fragmentation of the acetonitrile-related adduct was utilised for the structural characterisation of the FAMEs separated by HPLC. The APCI-MS detection of FAMEs encompassed a full-spectrum scan (providing information on the number of carbons and double bonds) and a data-dependent MS/MS scan of the [M+C(3)H(5)N](+·) ions (the position of the double bonds). The utility of this approach was demonstrated using a mixture of FAMEs from blackcurrant-seed oil. All the unsaturated fatty acids known to exist in the sample were correctly identified and several others were newly discovered. In terms of sensitivity, HPLC/APCI-MS appeared to be comparable to GC/EI-MS.
Keywords: mastné kyseliny; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Plant Oils; oleje rostlin; Tandem Mass Spectrometry; Chromatography, Reverse-Phase; Linolenic Acids; kyseliny linolenové; Fatty Acids; chromatografie s reverzní fází; vysokoúčinná kapalinová chromatografie